Impact of COVID-19 on the private and professional lives of highly educated women working in global health in Europe—A qualitative study - Hoffmann, Christina; Schneider, Tamara; Wannous, Chadia; Nyberger, Karolina; Haavardsson, Ingeborg; Gilmore, Brynne; Quigley, Paula; Winkler, Andrea S.; Ludwig, Sabine (Frontiers in Global Women's Health, 2023)
Background The COVID-19 pandemic has led to a deepening of existing inequalities and a rollback of achievements made in gender equality. Women in Global Health (WGH) is a global movement that aims to achieve gender equality in health and increase female leadership in global health. Here, the aim was to understand how the pandemic affects the private and professional lives of women working in global health in different European countries. Suggestions for future pandemic preparedness including how gender perspectives should be integrated into pandemic preparedness and how a women's network such as WGH helped them to overcome the impact of the pandemic were explored. Methods Qualitative semi-structured interviews were conducted in September 2020 with a sample size of nine highly educated women with a mean age of 42.1 years from the different WGH European chapters. The participants were informed of the study and were formally asked for their consent. The interviews were held in English via an online videoconference platform and lasted 20–25 min each. The interviews were audio recorded and transcribed verbatim. Thematic analysis was conducted according to Mayring Qualitative Content Analysis using MAXQDA. Results The pandemic has both positive and negative effects on the professional and private lives of women. It led to an increased workload and stress as well as pressure to publish on COVID-19-related themes. Increased childcare and household responsibilities represented a double burden. The available space was limited if other family members were also working from home. Positive aspects included more time for family or partners and reduced travel. The participants report on perceived gender differences in the experience of the pandemic. International cooperation is considered to be a key factor for future pandemic preparedness. Being part of a women's network such as WGH was perceived as being very supportive in difficult situations during the pandemic. Conclusion This study provides unique insights into the experiences of women working in global health in different European countries. The COVID-19 pandemic influences their professional and private lives. Perceived gender differences are reported and suggest the need for integrating gender perspectives in pandemic preparedness. Networks for women, such as WGH, can facilitate the exchange of information in crises and provide women with professional and personal support.